Synthetic platform for mono-functionalised tridentate macrocycles as key precursors of mechanically-linked macromolecular systems. Issue 11 (15th March 2021) - Sharma, Atul Kumar; Malineni, Jagadeesh; Box, Simon; Ghiassinejad, Sina; van Ruymbeke, Evelyne; Fustin, Charles-André
Abstract : Macrocycles bearing a variety of functional groups give access to a wide range of synthetic methods for further derivatisation or preparation of more complex structures such as mechanically interlocked molecules or polymeric materials. Abstract : We report here a synthetic platform toward mono-functionalized tridentate macrocycles based on a pyridine-2, 6-bis-carboxamide motif. These macrocycles bear a variety of functional groups at the fourth position of the pyridine, giving access to a wide range of synthetic methods for further derivatisation or preparation of more complex structures such as mechanically interlocked molecules or polymer materials. To illustrate the potential of this family of macrocycles a series of square planar palladium complex-based pseudorotaxanes, containing different axles and functional groups on the ring, are synthesised, and then used to prepare a macro-pseudorotaxane, i.e. a polymer containing a rotaxane junction, and mechanically-linked gels by a one-pot and a polyrotaxane approach.